Schistosomus reflexus in indigenous Ethiopian sheep - Mukasa-Mugerwa, E.; Tekelye Bekele (1989)
Part of a research project carried at Addis Ababa abattoir to study ovarian activity and gastro-intestinal parasitism in sheep.